The First Five Year Plan 1951-56: Summary of Recommendations - Planning Commission, Government of India (Planning Commission, Government of India, 1951)
Democratic planning and public co-operation For democratic planning to proceed with necessary momentum and continuity, the programme adopted should reflect the unity of outlook and approach among the members of the party in power and should also enlist the support and co-operation from shades of opinion outside the party. Co-ordination of policies between the Centre and the States. The system of consultation and formulation of policies between the Centre and the States on the basis of the over-all national requirements should be strengthened. The National Development Council, which has been recently set up, is intended to secure this result. Establishment and co-ordination of the activities of regional and local organisations. Appropriate local, regional, and functional organisations with defined spheres of action and responsibility should be set up and their activities co-ordinated at various levels from the village upwards.
Government of India Planning Commission
Keywords: First Five Year Plan